2010
DOI: 10.3350/kjhep.2010.16.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Clinical courses after administration of oral corticosteroids in patients with severely cholestatic acute hepatitis A; three cases

Abstract: Acute hepatitis A is currently outbreaking in Korea. Although prognosis of acute hepatitis A is generally favorable, a minority of patients are accompanied by fatal complications. Severe cholestasis is one of the important causes of prolonged hospitalization in patients with acute hepatitis A. In such cases, higher chances of additional complications and increased medical costs are inevitable. We report three cases of severely cholestatic hepatitis A, who showed favorable responses to oral corticosteroids. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
0
8
1
2
Order By: Relevance
“…Steroid therapy was reported to provide no improvement in the clinical manifestations of viral hepatitis among 77 patients with acute hepatitis. 11,13 In conclusion, spontaneous clinical improvement was reported in some cases with cholestatic form of the disease. 4 However, use of corticosteroids may provide rapid correction of clinical manifestations in selected non-immunocompromised patients presenting with very severe symptoms associated with cholestasis or relapsing patients with prolonged cholestatic form of the disease under close supervision.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Steroid therapy was reported to provide no improvement in the clinical manifestations of viral hepatitis among 77 patients with acute hepatitis. 11,13 In conclusion, spontaneous clinical improvement was reported in some cases with cholestatic form of the disease. 4 However, use of corticosteroids may provide rapid correction of clinical manifestations in selected non-immunocompromised patients presenting with very severe symptoms associated with cholestasis or relapsing patients with prolonged cholestatic form of the disease under close supervision.…”
Section: Discussionmentioning
confidence: 72%
“…Experimental studies on animals have shown that corticosteroids provide beneficial effects by inhibiting synthesis of inflammatory cytokines and improving actions of mrp2. 11,12 For our patient, use of corticosteroid was deemed necessary due to a significantly elevated level (48 mg/dL) of total bilirubin (direct bilirubin 33.86 mg/dL) before steroid treatment, persistence of bilirubin elevations and particularly the presence of severe itching. It is interesting to note that Yoon et al reported three patients who started treatment with oral prednisolone at a dose of 30 mg/day despite having much lower levels of direct bilirubin (19, 27 and 31 mg/dL, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The exchange of nucleotides in the mid-section of the untranslated sector 5 may also intervene with the severity of the damage [1]. In addition, cytokines and other inflammatory promoters like TNF-α and IL1 play a role in causing cholestasis [2, 4].…”
Section: Discussionmentioning
confidence: 99%
“…Two children, who presented with higher total bilirubin values (patients 2 and 14) (Table 1), received a brief course of steroid therapy, with prompt reduction of hyperbilirubinemia (Yoon et al, 2010;Saboo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%